Axitinib in first-line for patients with metastatic papillary renal cell carcinoma: Results of the multicentre, open-label, single-arm, phase II AXIPAP trial. (April 2020) - Negrier, Sylvie; Rioux-Leclercq, Nathalie; Ferlay, Céline; Gross-Goupil, Marine; Gravis, Gwenaëlle; Geoffrois, Lionel; Chevreau, Christine; Boyle, Helen; Rolland, Frederic; Blanc, Ellen; Ravaud, Alain; Dermeche, Slimane; et al.
Abstract: Introduction: Papillary renal cell carcinoma (PRCC) represents 10%–15% of renal carcinomas. No standard treatments exist for metastatic PRCC (mPRCC) patients. Axitinib is indicated as second-line treatment in metastatic clear cell renal carcinoma, and we aim to assess the efficacy of this vascular endothelial growth factor receptor inhibitor in front line for mPRCC. Methods: This French multicentre phase II study AXIPAP enrolled untreated mPRCC patients, with measurable disease, Eastern Cooperative Oncology Group performance status ≤ 1 and adequate organ functions. PRCC had to be confirmed by histology expert central review. Axitinib was administered orally 5 mg twice daily. Primary end-point was progression-free rate at 24 weeks (24w-PFR) by central review. Results: Fifty-six patients were screened, and 44 included (13 type 1, 30 type 2 and 1 non-specified). The median follow-up was 32.0 (13.1–39.9) months. The 24w-PFR was 45.2% (95% confidence interval [CI], 32.6% to +∞), the objective response rate was 28.6% (95% CI, 15.7%–44.6%) (type 1: 7.7%; type 2: 35.7%). The overall median progression free survival was 6.6 months (95% CI, 5.5–9.2), 6.7 months (95% CI, 5.5–9.2) and 6.2 months (95% CI, 5.4–9.2) for type 1 and 2, respectively. Median overall survival was 18.9 months (95% CI, 12.8–not reached). Adverse events were as expected; grade 3–4 treatment-related adverse events were rare except hypertension (27%). Conclusions: Axitinib demonstrated encouraging efficacy in mPRCC patients, especially in type 2 PRCC. Toxicity was manageable. Axitinib appears as an interesting option for first-line treatment and to be worth further investigation in combination with immunotherapy in these patients. Expert pathology review should be recommended in this setting. Clinical trial registration: ClinicalTrials.gov, NCT02489695. Highlights: No standard treatments exist for mPRCC patients. Axitinib showed encouraging results in mPRCC patients, especially in type 2 PRCC, and toxicity was manageable. Axitinib appears as an interesting agent to investigate in combination with immunotherapy in mPRCC patients. Expert pathology review to confirm PRCC should be recommended.